2020
DOI: 10.1016/j.jiac.2020.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged presence of SARS-CoV-2 in a COVID-19 case with rheumatoid arthritis taking iguratimod treated with ciclesonide

Abstract: We report a coronavirus disease 2019 (COVID-19) case with rheumatoid arthritis taking iguratimod. The patient who continued iguratimod therapy without dose reduction was treated with ciclesonide had an uneventful clinical course, but prolonged detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was observed after resolution of symptoms. The effects of disease-modifying antirheumatic drugs (DMARDs) and ciclesonide on clinical course and viral shedding remain unknown and warrant further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The treatment regime involves inhalation of 400 μg ciclesonide (two or three times per day; total, 1200 μg/day) for 2 weeks. Three cases of COVID-19 pneumonia treated successfully with ciclesonide have been reported on November 2, 2020 by guest http://jvi.asm.org/ Downloaded from (28), as have several case reports (29)(30)(31). None of these studies reported significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment regime involves inhalation of 400 μg ciclesonide (two or three times per day; total, 1200 μg/day) for 2 weeks. Three cases of COVID-19 pneumonia treated successfully with ciclesonide have been reported on November 2, 2020 by guest http://jvi.asm.org/ Downloaded from (28), as have several case reports (29)(30)(31). None of these studies reported significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment regime involves inhalation of 400 μ g ciclesonide (two or three times per day) for 2 weeks. Three cases of COVID-19 pneumonia treated successfully with ciclesonide have been reported (15), as have several case reports (16)(17)(18). None of these studies reported significant side effects.…”
Section: Introductionmentioning
confidence: 94%
“…23 Recently, various studies found that people developed arthritis after having COVID-19 (Table 1). COVID-19 has been reported to be associated with RA, 24,25 psoriatic arthritis, 26 reactive arthritis, 9,27,28 seronegative erosive arthritis, 29 chronic arthritis, 30 etc. Despite ongoing research, our comprehension of COVID-19-associated arthritis is currently limited.…”
Section: Introductionmentioning
confidence: 99%